PERAN HUMAS DALAM MEMBANGUN CITRA ORGANISASI DI RS ORTOPEDI PROF. DR. R. SOEHARSO SURAKARTA - Biyantara (Prodi Ilmu Komunikasi Universitas Sahid Surakarta, 2023)
The role of public relations in an organization is significant for the company's progress. It s is because they are responsible for creating an image and reputation for the external public by establishing mutually beneficial relationships with the government, the press, customers, and the local community. The descriptive qualitative research uses the data source triangulation technique as a data validity test. The results show that the role of public relations in building organizational image at Prof Dr. R Soeharso Orthopedi Hospital is carried out with a role as a communicator that is established between public relations and internal and external parties of the organization. Public relations is establishing relationships with internal and external parties of the organization. Back- up management is planning and implementing programs, and a corporate image is carried out by building a positive image through quality service and maintaining the company's good name.